Electromagnetic navigation bronchoscopy: clinical utility in the diagnosis of lung cancer - Seijo LM (Dove Medical Press, 2016)
Luis M Seijo Pulmonary Department, Instituto de Investigación Sanitaria-Fundación Jimenez Díaz-Centro de Investigación Biomedica en Red Enfermedades Respiratorias, Madrid, Spain Abstract: Electromagnetic navigation bronchoscopy (ENB) is one of several technological advances which have broadened the indications for bronchoscopy in the diagnostic workup of lung cancer. The technique facilitates bronchoscopic sampling of peripheral pulmonary nodules as well as mediastinal lymph nodes, although wide availability and expertise in endobronchial ultrasonography has limited its application in routine clinical practice to the former. ENB in this setting is quite versatile and may be considered an established alternative to more invasive techniques, especially in selected patients with underlying pulmonary disease or comorbidities at high risk for complications from computer topography-guided fine needle aspiration or surgical resection. Nodule sampling may be performed with a variety of instruments, including forceps, cytology brushes, and transbronchial needles. Although samples are generally small, they are often suitable for molecular analysis. Keywords: lung cancer, ENB, electromagnetic navigation, bronchoscopy, diagnosis, pulmonary nodule